Nobody’s gesture. Paradossalità del gesto nella pittura di Flavia Albu (Materiali di Estetica. Terza serie, 2025)
The essay probes Flavia Albu’s strategy of staging a gesture without origin in her recent paintings. Mobilising Peirce’s idea of the index as revisited by Rosalind Krauss (1977), it argues that Albu’s meticulously painted brushstrokes emulate digital prints, thereby cutting the customary chain psyche-hand- mark. In her diptychs, imageduplication converts the simulated stroke into a selfreferential icon, foregrounding the differential play that unsettles claims to immediacy, presence and authorship. The text ultimately places Albu in a conceptual lineage that uses painterly illusion to critique medium specificity and expressive mythologies.
Keywords: Flavia Albu; digital art; abstract art